Twentieth workshop on geothermal reservoir engineering: Proceedings - United States. Department of Energy. Office of Energy Efficiency and Renewable Energy. (Stanford University, 1995)
PREFACE The Twentieth Workshop on Geothermal Reservoir Engineering, dedicated to the memory of Professor Hank Ramey, was held at Stanford University on January 24-26, 1995. There were ninety-five registered participants. Participants came from six foreign countries: Japan, Mexico, England, Italy, New Zealand and Iceland. The performance of many geothermal reservoirs outside the United States was described in several of the papers. Professor Roland N. Horne opened the meeting and welcomed visitors to the campus. The key note speaker was Marshall Reed, who gave a brief overview of the Department of Energy's current plan. Thirty-two papers were presented in the technical sessions of the workshop. Technical papers were organized into eleven sessions concerning: field development, modeling, well tesubore, injection, geoscience, geochemistry and field operations. Session chairmen were major contributors to the workshop, and we thank: Ben Barker, Bob Fournier, Mark Walters, John Counsil, Marcelo Lippmann, Keshav Goyal, Joel Renner and Mike Shook. In addition to the technical sessions, a panel discussion was held on ''What have we learned in 20 years?'' Panel speakers included Patrick Muffler, George Frye, Alfred Truesdell and John Pritchett. The subject was further discussed by Subir Sanyal, who gave the post-dinner speech at the banquet. The Workshop was organized by the Stanford Geothermal Program faculty, staff, and graduate students. We wish to thank our students who operated the audiovisual equipment. Shaun D. Fitzgerald Program Manager